The Analysis of Student’s Problem Solving Difficulty Viewed From Adversity Quotient on Means-Ends Analysis Learning - Rinawati, Sulis; Waluya, St. Budi; Hartono, Hartono (Unnes Journal of Mathematics Education Research, 2019)
The purpose of this study is (1) to describe the quality of Means-Ends Analysis (MEA) learning in contextual nuances and (2) to analyze students' difficulties in Zalina's problems solving in terms of adversity quotient. The type of research used is mixed concurrent embedded model methods. The population of this study were students of class X MIPA SMA N 1 Gubug, Grobogan. The research subject was determined based on the adversity quotient category, namely quitter, camper, and climber. Data collection techniques in the form of questionnaires, observation, tests, and interviews. The results showed that (1) contextual MEA learning is qualitatively and quantitatively qualified (2) students' problem solving abilities quittered to the point of understanding the problem and achieving the first problem solving indicator, the student camper could solve the problem until the stage of expressing the answer and achieving all solving indicators problem, climber students can solve the problem until the stage states the answer and reaches all the problem solving indicators.